RANCANG BANGUN MESIN UKIR BAKAR BERBASIS ARDUINO UNO - -, Inda; Nuhgraha, Yoddy Agung (Jurnal Mahasiswa Terapan, 2025)
Burn engraving artisans still use tools similar to soldering pens in their crafting process. Burn engraving art is manually created using the skills of the artisans. Burn engraving machines play a significant role in the burning process when producing this art. Therefore, this study aims to develop a more precise, efficient, and reliable solution for the burning process using a burn engraving machine. Additionally, this study also seeks to design a burn engraving machine based on Arduino Uno. The research methods include a literature review, tool preparation, and material selection for the frame construction. The frame is a crucial component in machine design as it supports the load during machine operation. The von Mises stress simulation results show values of 3.408 N/mm² (MPa) and 6.470 N/mm² (MPa).